Strategies of labour behaviour of Belarusians living in territories contaminated with radionuclides - Lashuk, Iryna V.; Kargapolova, Ekaterina V. (Journal of the Belarusian State University. Sociology, 2023)
The purpose of this work is to identify the specifics of labour behaviour strategies of residents of territories affected by the Chernobyl accident. The results of the study show that every fifth respondent in the studied regions is afraid of losing his job and doubts that he can find an equivalent job in his locality. In Gomiel and Mogiliov regions, the situation in this regard is more tense than in Brest. This can lead to an increase in social tension and migration sentiment in the studied territories. In these conditions, the development of small and medium-sized businesses is a effective step to improve the level and quality of life of residents, which will subsequently lead to an increase in economic indicators in these regions. It is necessary to step up efforts to create conditions under which the labour potential could be realised within the affected regions.